Cardiopulmonary performance during maximal exercise in soccer players with alterations in renal function - Pontes Morales, A.; Sampaio-Jorge, F.; da Cruz Rangel, L. F.; de Souza Menezes, J.; Costa Leite, T.; Goncalves Ribeiro, B. (Journal of Human Kinetics, 2017)
The aim of this study was to evaluate the curves of cardiorespiratory variables during cardiopulmonary exercise testing (CPET) in soccer players who had acute alterations in the glomerular filtration rate (GFR) after performing the pre-season training protocol. Sixteen male professional soccer players (25 ± 3 years; 179 ± 2 cm; and 77 ± 6 kg) were evaluated for oxygen uptake (VO2), heart rate (HR) and pulse relative oxygen (relative O2 Pulse) curves with intervals corresponding to 10% of the total duration of CPET. Athletes were grouped according to the GFR and classified as decreased GFR (dGFR; n = 8) and normal GFR (nGFR; n = 8). Athletes from the dGFR group exhibited lower VO2 values (p < 0.05) when 90% (dGFR 49.8 ± 4.0 vs. nGFR 54.4 ± 6.1 ml·kg-1·min-1) and 100% (dGFR 52.6 ± 4.1 vs. nGFR 57.4 ± 5.9 ml·kg-1·min-1) of the test was complete; HR high values (p < 0.05) when 90% (dGFR 183.7 ± 5.1 vs. nGFR 176.6 ± 4.8 bpm-1) and 100% (dGFR 188.1 ± 5.0 vs. nGFR 180.8 ± 4.8 bpm-1) of the test was complete; and lower relative O2 Pulse values (p < 0.05) when 70% (dGFR 25.6 ± 8.4 vs. nGFR 27.9 ± 9.7 ml·beat-1·kg-1), 80% (dGFR 26.6 ± 8.8 vs. nGFR 29.1 ± 10.0 ml·beat-1·kg-1), 90% (dGFR 27.1 ± 9.0 vs. nGFR 30.8 ± 10.6 ml·beat-1·kg-1) and 100% (dGFR 28 ± 9.2 vs. nGFR 31.8 ± 10.9 ml·beat-1·kg-1) of the test was complete. A correlation was found (r = -0.66, R2 = 0.44, p = 0.00) between lower VO2 peak and elevated levels of urinary protein excretion. In conclusion, soccer players with reduced kidney function after performing the pre-season training protocol also presented alterations in cardiopulmonary variables. We suggest that monitoring of renal function may be used to identify less conditioned soccer players.